Reviewing the Effect of English as a Foreign Language Teachers’ Positive and Negative Affectivity on Their Work Engagement - Fan, Yuguo (Frontiers in Psychology, 2022)
This review strives to illuminate the related studies on the effect of English as a Foreign Language (EFL) teachers’ positive and negative emotions on their work engagement. The negative correlations among teachers’ boredom, apprehension, shame, frustration, and work engagement have been confirmed in the review of the literature. Furthermore, few studies have validated the effect of teachers’ positive emotions, such as enjoyment and pride on their work engagement in educational contexts. The studies showed that some factors, such as teacher self-efficacy, teacher self-sufficiency, increased educational challenges, and ambiguity in educational contexts, can mediate the relationship between teachers’ negative emotions and work engagement. The review of literature has emphasized the mediating role of growth mindset in the relationship between teachers’ positive emotions and work engagement. In order to improve the language teaching quality, the pedagogical implications are explained in the end. Some suggestions for further research are provided to expand the literature about teachers’ emotional variables.